2008 38th Annual Frontiers in Education Conference 2008
DOI: 10.1109/fie.2008.4720469
|View full text |Cite
|
Sign up to set email alerts
|

T-Bot and Q-Bot: A couple of AIML-based bots for tutoring courses and evaluating students

Abstract: Intelligent Tutoring Systems are computer programs that aim at providing personalized instruction to students. In recent years, conversational robots, usually known as chatterbots, become very popular in the Internet, and ALICE (Artificial Linguistic Internet Computer Entity) is probably the most popular one. ALICE brain is written in AIML (Artificial Intelligence Markup Language), an open XML language. We consider the combination of both approaches, i.e, the use of AIML-based bots for tutoring purposes in ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 7 publications
0
5
0
1
Order By: Relevance
“…Analyzing chatterbot development from the viewpoint of NLP, we can identify three generations of these systems [17]:…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Analyzing chatterbot development from the viewpoint of NLP, we can identify three generations of these systems [17]:…”
Section: Related Workmentioning
confidence: 99%
“…Mikic, F.A., Burguillo, J.C., Rodríguez, D.A., Rodríguez, E., Llamas, M. [17] developed a couple of AIML-based Bots for tutoring courses and evaluating students. Intelligent Tutoring Systems are computer programs that aim at providing Personalized instruction to students.…”
Section: T-bot and Q-botmentioning
confidence: 99%
See 1 more Smart Citation
“…Penelitian tentang penggabungan tutor bot (T-Bot) dan evaluation bot (Q-Bot) efektif untuk membantu siswa selama proses belajar mengajar dan mendukung pengajar untuk melakukan aktivitas mengajar [5]. Penelitian ini menggunakan AIML berbasis PHP (Program E) yang dikombinasikan dengan sistem e-learning Claroline dan Moodle.…”
Section: A Chatterbotunclassified
“…The range of systems also demonstrated that the chatbot-learning approach was very versatile and flexible. Mikic et al, (2008) introduced a tutor bot (T-Bot) which answers students' questions about different courses and subjects that are available via e-learning platform using natural language. Freeling, an open-source linguistic analyser, to extract candidate keywords and concepts related to course contents.…”
Section: Figure 3 Corpus-based Approach To Building a Natural Languamentioning
confidence: 99%